PERLINDUNGAN HUKUM INTERNASIONAL TERHADAP SILEK LINTAU SEBAGAI KEBUDAYAAN ASLI SUMATERA BARAT BERDASARKAN UNESCO CONVENTION FOR THE SAFEGUARDING OF THE INTAGIBLE CULTURAL HERITAGE 2003 - M.Aidil Akbar; Zulfikar Jayakusuma; Aditiara Putri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Cultural heritage is a nation's indispensable identity to promote Indonesia'snational culture. Cultural heritage includes the culture of tangible culturalheritage and intangible cultural heritage. Indonesia's cultural heritage that hasbeen registered and managed by the Directorate General of Culture to date hasamounted to 594 cultural works. The cultural work consists of 137 people'scustoms, rites and celebrations; 160 works of traditional skills and crafts; 31cultural works in the field of knowledge and behavioral habits concerning theuniverse; 69 in the field of tradition and oral expression, as well as 197 culturalworks related to performing arts. Silek Lintau is one of the performing arts.Currently Silek Lintau is more popular in foreign country than in Indonesia, soSilek Lintau needs to be protected.This study uses a sociological legal research typology or so-called nondoctrinallegal research, more specifically discussing the effectiveness of the law.In this study the author uses the nature of descriptive research, because theauthors describe Implementation of Unesco Convention For The Safeguarding OfThe Intangible Cultural Heritage 2003 In Protecting Silek Lintau. The results ofthe research conducted by the author is, first Silek Lintau can be protectedinternationally through Convention UNESCO Convention For The SafeguardingOf The Intangible Cultural Heritage 2003. Besides can be protected through theRegime of UNESCO 2003, Silek Lintau can also be protected through IntellectualProperty Rights Regime, at UNESCO Convention On The Protection AndPromotion Of The Diversity Of Cultural Expression 2005. Central and localgovernments are obliged to advance the culture of the Indonesian nation. Inprotecting the culture, there are various obstacles, including the erosion ofcultural values due to lack of appreciation from the younger generation. Theshort-term solution that government can do is to promote a culture in variousevents, both at home and abroad.Keywords: Protection - International - Silek Lintau - UNESCO Convention